2015
DOI: 10.1155/2015/521481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nutritional Status of Patients with Depression

Abstract: Aims and Objectives. Our goal was to determine nutritional status, body composition, and biochemical parameters of patients diagnosed with depression based on DSM-IV-TR criteria. Methods. A total of 59 individuals, aged 18–60 years admitted to Mental Health Centre of Kayseri Education and Research Hospital, were included in the study. The participants were randomly assigned to two groups; depression group (n = 29) and control group (n = 30). Anthropometric measurements, some biochemical parameters, demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 73 publications
3
47
1
4
Order By: Relevance
“…These intakes estimated at 249.91 g/day were significantly greater than controls (p=0.0001). Our results are comparable to Gülşah Kaner [32] and Ben Smail [33]. In Iran, a contribution of 318.6 g/d was found in the study of Pourghassem Gargari [27], whose purpose was to determine the relationship between nutrient intake and the severity of depression.…”
Section: Discussionsupporting
confidence: 86%
“…These intakes estimated at 249.91 g/day were significantly greater than controls (p=0.0001). Our results are comparable to Gülşah Kaner [32] and Ben Smail [33]. In Iran, a contribution of 318.6 g/d was found in the study of Pourghassem Gargari [27], whose purpose was to determine the relationship between nutrient intake and the severity of depression.…”
Section: Discussionsupporting
confidence: 86%
“…However, a gluten-free diet has not been shown to significantly improve ADHD symptoms in children who have not been diagnosed with celiac disease, an autoimmune disorder that is triggered by ingestion of gluten (90). their calories as CHOs, and nondepressed individuals consumed 50% of their calories as CHOs; however, there was no significant difference (P = 0.055) between the two groups (103). In a much larger study of nearly 1,000 homebound elderly individuals who were or were not depressed, there was no difference in total CHO intake (104).…”
Section: Diet and Treatment Of Adhdmentioning
confidence: 84%
“…Several studies have shown that major depression is directly related to change in appetite, consumption of high caloric foods, weight gain, constipation, dehydration, and change in serum vitamin-minerals levels (Kaner et al, 2015). Furthermore, change in eating behaviours of major depression patients may cause various problems in the treatment of depression.…”
Section: Introductionmentioning
confidence: 99%